Relooking at the Common Core Standards Through the Lens of Equity – Closing the Achievement Gap - Rathee, N. K. (European Scientific Journal, ESJ, 2017)
On the failure of No Child Left Behind (NCLB) to close the “achievement gap” between whites and minorities, the Common Core State Standards were heralded as the best way of raising academic standards for all children around the country and closing the achievement gap. Numerous reports have emerged questioning the efficacy of the Common Core Standards to deliver what was promised. Public disillusion is apparent. This paper is an attempt to revisit the Common Core Standards through the lens of data generated by its implementation. Quantitative data available from the National Assessment of Educational Progress (NAEP) for 4th, 8th and 12th grade students and their achievements scores for mathematics and reading for the years 2009, 2011, 2013 and 2015 were taken into consideration. Results have revealed no increase, much less significant, in the average achievement scores and no indication that the achievement gap was being narrowed. Recommendations have been made for having a relook at the content and the implementation of the standards.